Doctoral dissertations in logistics and supply chain management: a review of Nordic contributions from 2009 to 2014 - Christopher Rajkumar; Lone Kavin; Xue Luo; Jan Stentoft (Logistics Research, 2016)
The purpose of this paper is to identify and analyze Nordic doctoral dissertations in logistics and supply chain management (SCM) published from the years 2009-2014. The paper is based on a detailed review of 150 doctoral dissertations. Compared with previous studies, this paper identifies a trend toward: more dissertations based on a collection of articles than monographs; more dissertations focusing on inter-organizational SCM issues; a shift from a focal company perspective to functional aspects and supply chain-related research; and finally, a continued decreased focus on the philosophy of science. A score for measuring the significance of article-based dissertations is also proposed.
Keywords: 650; Doctoral dissertations; Collection of articles; Monographs; Dissertation score; Logistics and supply chain management